Study of the effect of feeding Tenebrio molitor larvae during their rearing on their growth, nutritional profile, value and safety of the produced flour - Konstantina Papastavropoulou; Anastasia Koupa; Evangelia Kritikou; Marios Kostakis; Sofia Dervisoglou; Andreas Roussos; Dionysios Perdikis; Nikolaos S. Thomaidis; Emel Oz; Fatih Oz; Charalampos Proestos; Haizhou Wu (Food Chemistry: X)
Science and food industry must strive to ensure and improve edible insect's benefits, and especially their safety and nutritional value. This study investigated how various food substrates used in the rearing of Tenebrio molitor larvae influence their growth, the safety of the larvae, and the nutritional quality of the resulting flour. The main findings indicate that all samples showed significant differences in their nutritional profile, larval characteristics, and heavy metal content. Regarding the content of protein, fat and fiber it ranges from 44.1 to 51.8 %, 28.6–34.8 % and 10.5–14.9 %, respectively. These results suggest that insect diet is a very crucial parameter that can affect all that factors and must be taken into account, especially when they are intended as raw materials to be used for food production.